2017
DOI: 10.3389/fpls.2017.01916
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Trait Heritability, Training Population Size and Marker Density on Genomic Prediction Accuracy Estimation in 22 bi-parental Tropical Maize Populations

Abstract: Genomic selection is being used increasingly in plant breeding to accelerate genetic gain per unit time. One of the most important applications of genomic selection in maize breeding is to predict and select the best un-phenotyped lines in bi-parental populations based on genomic estimated breeding values. In the present study, 22 bi-parental tropical maize populations genotyped with low density SNPs were used to evaluate the genomic prediction accuracy (rMG) of the six trait-environment combinations under var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

27
96
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 154 publications
(125 citation statements)
references
References 44 publications
(69 reference statements)
27
96
2
Order By: Relevance
“…Additionally, in a progeny row scenario, selections using GS can be made prior to harvest, improving the efficiency in comparison with PS. In contrast with this study, Zhang et al (2017) observed increased GS prediction accuracy for maize (Zea mays L.) with increased training population and marker densities. Although this study used the Infinium beadchip SoySNP50K (Song et al, 2013) for genotyping, many soybean studies have begun genotyping with the less dense BARCSoySNP6k array (Song et al, 2014).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Additionally, in a progeny row scenario, selections using GS can be made prior to harvest, improving the efficiency in comparison with PS. In contrast with this study, Zhang et al (2017) observed increased GS prediction accuracy for maize (Zea mays L.) with increased training population and marker densities. Although this study used the Infinium beadchip SoySNP50K (Song et al, 2013) for genotyping, many soybean studies have begun genotyping with the less dense BARCSoySNP6k array (Song et al, 2014).…”
Section: Discussioncontrasting
confidence: 99%
“…For yield, the predictions were most accurate when the training population and the test population were identical. In contrast with this study, Zhang et al (2017) observed increased GS prediction accuracy for maize (Zea mays L.) with increased training population and marker densities. Continued refinement of training population and marker densities will be essential for maximizing the efficiency of GS in soybean breeding operations.…”
Section: Traitcontrasting
confidence: 99%
“…The high heritabilities (> 0.8) computed for the traits 100GW, EH and PH indicate the confidence of the transmission of the traits to future generations, directly influencing the selection gains (1). The high correlation of heritability with accuracy found agrees with results of (4143). According to (43), when breeders outline the phenotyping experiments for GS, they should consider that the heritability of the traits of interest in the training population should be high to ensure a satisfactory predictive accuracy.…”
Section: Discussionsupporting
confidence: 89%
“…The high correlation of heritability with accuracy found agrees with results of (4143). According to (43), when breeders outline the phenotyping experiments for GS, they should consider that the heritability of the traits of interest in the training population should be high to ensure a satisfactory predictive accuracy. To this end, the number of locations and replications should be increased.…”
Section: Discussionsupporting
confidence: 89%
“…For those heritable traits, prediction of the phenotype or risk using DNA can usually reach moderately high prediction accuracy (de los Campos et al, 2018). Thus, GP tends to increase prediction accuracy with higher heritability (Zhang et al, 2017). In general, high-heritability traits, including flowering time in plants and human height, have already been studied (de Oliveira et al, Lello et al, 2018).…”
mentioning
confidence: 99%